(untitled) (KULT_online, 2012)
The South African Trade Union Movement, part of the anti-apartheid-struggle and shaper of the democratic transition process, has maintained its influential societal position until today. However, trade unions are not only important agents of change, but also subjects liable of change. In this perspective and in line with the Labour Revitalization Studies, Sakhela Buhlungu analyses dilemmas of Union Organising in the face of changing societal conditions. In his comprehensive analysis the author observes a paradox of victory of the major trade union umbrella organisation in South Africa, COSATU, between its increase of political influence on the one hand and the diminishing of its organisational power on the other hand.